2023
DOI: 10.1002/phar.2776
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between partial thromboplastin time and thromboelastography in adult critically ill patients requiring bivalirudin for extracorporeal membrane oxygenation

Abstract: Study Objective Thromboelastography (TEG) offers a more dynamic assessment of hemostasis over activated partial thromboplastin time (aPTT). However, the clinical utility of TEG in monitoring bivalirudin during extracorporeal membrane oxygenation (ECMO) remains unknown. The purpose of this study was to evaluate the correlation between aPTT and TEG in adult ECMO patients anticoagulated with bivalirudin. Design Multicenter, retrospective, cohort study conducted over a 2‐year period. Setting Two academic universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A retrospective study evaluating 106 ROTEM analyses from pediatric patients receiving bivalirudin infusion during receipt of ECMO ( n = 6) or ventricular assist devices ( n = 12) found that prolonged clotting time on the INTEM assay had a moderate to strong correlation with aPTT ( r = 0.54, p < 0.0001) 63 . A multicenter, retrospective, cohort study of 104 adult patients receiving ECMO and bivalirudin similarly found a moderate correlation between TEG R time and aPTT across 848 concurrent laboratory assessments ( r = 0.41, p < 0.001) 64 . These studies provide preliminary evidence for ROTEM as a potential alternative to standard aPTT assays for monitoring bivalirudin during ECMO; however, a comparison of safety and clinical outcomes with ROTEM versus aPTT‐based monitoring of bivalirudin is warranted before changing standard monitoring techniques.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 98%
“…A retrospective study evaluating 106 ROTEM analyses from pediatric patients receiving bivalirudin infusion during receipt of ECMO ( n = 6) or ventricular assist devices ( n = 12) found that prolonged clotting time on the INTEM assay had a moderate to strong correlation with aPTT ( r = 0.54, p < 0.0001) 63 . A multicenter, retrospective, cohort study of 104 adult patients receiving ECMO and bivalirudin similarly found a moderate correlation between TEG R time and aPTT across 848 concurrent laboratory assessments ( r = 0.41, p < 0.001) 64 . These studies provide preliminary evidence for ROTEM as a potential alternative to standard aPTT assays for monitoring bivalirudin during ECMO; however, a comparison of safety and clinical outcomes with ROTEM versus aPTT‐based monitoring of bivalirudin is warranted before changing standard monitoring techniques.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 98%